Introduction to Dossier. Dimensions of Politics and Political Brokerage: Skills, Scales, Resources and Trajectories - Edison Hurtado Arroba; Martín Paladino; Gabriel Vommaro (Íconos)
This article presents an analytical overview of the topic of political operators, politicians and political professionals drawing on the literature and empirical research including sociological approaches, ethnographic work and the specialized literature. Drawing on the sociology of political practice, a definition of political work is developed which centres on three aspects: the skills and practical abilities that politicians develop, the resources that are employed and the outputs of political practice. From here, we propose and dissect a range of key analytic dimensions (scales of action, resources, skills, careers and trajectories) to configure the objectives for research on this topic from the everyday practices of politicians and political professionals. Finally, we situate different modes of political practice within the broader social worlds in which they exist.